Review on Managing Climate Change and ESG Risks in Financial Market - Mohamad Shafi, Roslina; Abu Bakar, Norsaliza (Journal of Entrepreneurship, Business and Economics, 2022)
Climate change and environmental issues have an impact on the overall stability of the financial system. Intermediaries that operate on a long-term horizon are exposed to the consequences of extreme environmental events. Banking sectors and insurance companies could be the most vulnerable and sensitive to these issues. Consequently, the aims of this paper is to review recent development on the risk frameworks developed by regulators and to classify the climate-related risks, and to explore whether these risks affecting the costs and benefits that is related to organizations. Research paper Keywords: Climate change; environmental risks; governance; risk frameworks; systemic risk, finance Reference to this paper should be made as follows: Mohamad Shafi, R., & Abu Bakar, N. (2022). Review on Managing Climate Change and ESG Risks in Financial Market. Journal of Entrepreneurship, Business and Economics , 10 (2), 44–62.